(untitled) (Texas Journal of Philology, Culture and History, 2021)
This paper aims to investigate the defense mechanisms in the short story Your Eyes are my Destiny, which is the first story in a short story collection with the same name by Syrian poet and writer, Ghada al-Samman. She explores feminine themes in her works. In his psychological theory, Freud divides human psyche to three different parts: id, ego, and superego. Freud believes that id is the biggest part in the psychic apparatus of personality which includes human primitive instincts and motives. The ego is the intellectual and rational component of personality. it is a conscious part which operates according to the reality principle. The superego is the last stage of psychic development and incorporates the values and morals of society. Defense mechanism are unconscious behaviors used by ego to lessen the anxiety resulted from imbalance between id and superego desires. The basis of all defense mechanisms is repressing id impulses and distancing from reality. Powerful characterization in Your Eyes are my Destiny has enabled Samman to depict such mechanisms in her protagonist, Tal’at. In this paper, some of the defense mechanisms employed in Samman’s story are discussed.